2005
DOI: 10.1016/j.mam.2005.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional aspects of manganese homeostasis

Abstract: Manganese (Mn) is an essential mineral. It is present in virtually all diets at low concentrations. The principal route of intake for Mn is via food consumption, but in occupational cohorts, inhalation exposure may also occur (this subject will not be dealt with in this review). Humans maintain stable tissue levels of Mn. This is achieved via tight homeostatic control of both absorption and excretion. Nevertheless, it is well established that exposure to high oral, parenteral or ambient air concentrations of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
569
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 747 publications
(587 citation statements)
references
References 52 publications
(58 reference statements)
8
569
2
8
Order By: Relevance
“…However, there is increasing evidence that health effects of toxic metals differ in prevalence or are manifested differently in men and women (Vahter et al 2007;Lee & Kim 2014), which is in the line of the results obtained in this study. Moreover, gender differences in the absorption of Mn are well documented, with men absorbing significantly less Mn compared to women depending on their Fe status (Finley et al 1994;Aschner & Aschner 2005), which is also in good agreement with the results presented here.…”
Section: The Relationships Found Between Bioaccessibility Estimates Asupporting
confidence: 92%
See 2 more Smart Citations
“…However, there is increasing evidence that health effects of toxic metals differ in prevalence or are manifested differently in men and women (Vahter et al 2007;Lee & Kim 2014), which is in the line of the results obtained in this study. Moreover, gender differences in the absorption of Mn are well documented, with men absorbing significantly less Mn compared to women depending on their Fe status (Finley et al 1994;Aschner & Aschner 2005), which is also in good agreement with the results presented here.…”
Section: The Relationships Found Between Bioaccessibility Estimates Asupporting
confidence: 92%
“…Although balance studies and excretion data indicate that low gastrointestinal absorption and rapid elimination of Mn limits its toxicity following the ingestion of high doses, it is well established that exposure to environmental Mn can result in elevated tissue Mn levels (Aschner & Aschner 2005;Santamaria 2008). Likewise, recent studies report elevated Cu levels determined in human biomarkers collected from people exposed to environmental Cu (Ndilila et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason that As was highest in spring and summer and Sb was highest in summer and fall is unknown, but may in part reflect increase in water intake during warm weather. The observed correlation between Se and Mn may reflect homeostatic processes related to these trace essential elements (Burk and Levander, 1999;Aschner and Aschner, 2005;Roth, 2006), and may not be related to exogenous exposure per se.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that the daily dietary intake of manganese by women below 1 mg causes altered mood in women during the premenstrual phase of their estrous cycle [37]. Manganese is neurotoxic at higher exposures, but it has been estimated that only 1-5% of ingested this biometal is absorbed in adults [2]. Manganese is considered an essential and critical nutrient, and its deficiency or overabundance may cause depressive disorders.…”
Section: Manganesementioning
confidence: 99%